Challenges of managing inflammatory bowel disease using biological therapies: a qualitative study from Iraq - Hasan Ali Owayez; Ali Lateef Jasim; Haider Jamal Mahmoud (Pharmacia)
In conflict-affected Iraq, managing inflammatory bowel disease using biologic therapies faces ongoing systemic challenges. Limited access to advanced diagnostic tools and a high prevalence of tuberculosis complicate the differentiation between Crohn’s disease and intestinal tuberculosis, often leading to misdiagnoses and inappropriate treatments. This qualitative study explores the difficulties faced by gastroenterologists and internists in providing IBD care in resource-limited settings. Semi-structured interviews with ten specialists at the Gastroenterology and Hepatology Teaching Hospital in Baghdad identified key themes: diagnostic uncertainties, clinician skepticism about biosimilars, medication shortages, patient adherence issues, follow-up barriers, infrastructural limitations, and the need for systemic reforms. Delays in histopathological analysis and limited diagnostic capacity, coupled with high tuberculosis incidence, increase misdiagnoses and antibiotic resistance. The shortage of original biologics has resulted in reliance on anti-TNF agents, while newer therapies remain inaccessible. Establishing specialized IBD clinics, centralizing drug procurement, improving diagnostic capabilities, and adopting interdisciplinary management are vital steps toward sustainable care. Collaborative policy reforms and international cooperation are essential to ensure equitable IBD treatment in this conflict-affected, low-resource environment.